Comparison of antimicrobial substantivity of root canal irrigants in instrumented root canals up to 72 h: An in vitro study - M N Shahani; V V Subba Reddy (Wolters Kluwer Medknow Publications, 2011)
Disinfection of the root canal system is one of the primary aims of root canal treatment. This can be achieved through the use of various antimicrobial agents in the form of irrigants and medicaments. The antimicrobial substantivity of 2% chlorhexidine gluconate, 1% povidone iodine, 2.5% hydrogen peroxide followed by 2% sodium hypochlorite, and 2% sodium hypochlorite alone as irrigants was assessed in instrumented root canals. 2% chlorhexidine showed antimicrobial substantivity lasting up to 72 h, followed by 1% povidone iodine, and 2% sodium hypochlorite. Thus 2% chlorhexidine should be used as a final rinse irrigant in endodontic treatment protocols.